2021
DOI: 10.1242/dmm.049159
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteriophage–antibiotic therapy promotes enhanced clearance of drug-resistant Mycobacterium abscessus

Abstract: Infection by multidrug-resistant Mycobacterium abscessus is increasingly prevalent in cystic fibrosis (CF) patients, leaving clinicians with few therapeutic options. A compassionate study showed the clinical improvement of a CF patient with a disseminated M. abscessus (GD01) infection, following injection of a phage cocktail, including phage Muddy. Broadening the use of phage therapy in patients as a potential antibacterial alternative necessitates the development of biological models to improve the reliabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…In addition to a mature innate immune system, zebrafish embryos are genetically similar to human, and their transparency make them ideal for investigating characteristics of infection mechanisms unreachable in standard animal models. Very recently, several zebrafish studies have been published for evaluating phage treatment upon bacterial infections, though none have studied S. aureus (Easwaran et al, 2017;Johansen et al, 2021;Sundaramoorthy et al, 2021). Bacteria can be injected into the embryo's bloodstream alongside phages, and this treatment was effective with a better survival of the infected zebrafish embryos.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In addition to a mature innate immune system, zebrafish embryos are genetically similar to human, and their transparency make them ideal for investigating characteristics of infection mechanisms unreachable in standard animal models. Very recently, several zebrafish studies have been published for evaluating phage treatment upon bacterial infections, though none have studied S. aureus (Easwaran et al, 2017;Johansen et al, 2021;Sundaramoorthy et al, 2021). Bacteria can be injected into the embryo's bloodstream alongside phages, and this treatment was effective with a better survival of the infected zebrafish embryos.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…In 2021, the result of a clinical trial on a patient with cystic fibrosis (CF) suffering from a prolonged disseminated infection with M. abscessus , Pseudomonas aeruginosa, EBV viremia (8 years), with a history of two lung transplantations along with administration of various oral/intravenous antibiotics, lumacaftor/ivacaftor, and immunosuppressive drugs (e.g., Clofazimine, bedaquiline, Mycophenolate mofetil, iv rituximab) revealed that the hypodermic administration of mycobacteriophages cocktail containing Muddy (wild type) and engineered BPs33ΔHTH-HRM10 and ZoeJΔ45 every 12 h for seven months (10 9 pfu/dose of each phage) could improve the recovery in this patient [ 16 , 17 , 196 ]. Furthermore, regarding the engineered phages used in the recent study, repressors that induce the lysogenic life cycle in these phages were deleted, and these phages were converted to lytic phages.…”
Section: Mycobacteriophages and Treatment Of Mycobacterial Infectionsmentioning
confidence: 99%
“…Evidence reveals that most M. abscessus -associated infections are multidrug resistant [ 16 ]. M. abscessus strain GD01 is one of the most-used strains successfully infected with and eliminated by mycobacteriophages such as Muddy, BPs, and ZoeJ [ 196 ].…”
Section: Mycobacteriophages and Treatment Of Mycobacterial Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…New measures against multi-drug resistant M. abscesses are intensively pursued, such as phage therapy [5,6], natural or synthetic antimicrobial peptide [7] and photodynamic therapy (PDT) [8]. PDT is an emerging treatment modality for diseases with the combination of photosensitive drugs and corresponding wavelengths of light.…”
Section: Introductionmentioning
confidence: 99%